Entrepreneurial ecosystem as a multilevel system of socio-economic development: theoretical analysis and typological approaches - Kornetskyy, Artem (Management and Entrepreneurship: Trends of Development, 2025)
The article examines the entrepreneurial ecosystem as a complex and adaptive system that integrates institutional, social, cultural, infrastructural, and network components. This multifaceted perspective underscores that the ecosystem is not limited to the actions of individual entrepreneurs but is profoundly shaped by dynamic interactions among various actors, including entrepreneurs, government bodies, educational organizations, financial institutions, and both local and global communities. The increasing relevance of this topic stems from the broader academic recognition that sustainable entrepreneurship depends on systemic influences and collaborative networks as much as personal initiative. The main objective of the paper is to provide a thorough analysis of contemporary theoretical approaches to defining entrepreneurial ecosystems, delineate their core structural elements and stages of evolutionary development, and to organize and classify prevalent models found in both international and Ukrainian contexts. The study’s methodological framework employs an interdisciplinary toolkit, combining systems thinking, evolutionary theory, and institutional analysis, to facilitate a holistic examination of the ecosystem’s characteristics and functioning. A critical distinction is drawn between state-driven and network-based ecosystem models and their respective impacts on fostering innovation, nurturing an entrepreneurial mindset, and generating social value. Furthermore, the article introduces a nuanced typology of ecosystem structures, considering sources of initiative, levels and mechanisms of support, the degree of social orientation, and measurable outcomes. Special attention is devoted to the Ukrainian experience, offering illustrative examples of regional initiatives, their adaptability, and prospects for scaling and co-evolution. In conclusion, the author stresses that successful entrepreneurial ecosystems are context-dependent and require strategic management tailored to local resources, culture, and socio-economic realities to drive sustained innovation and competitiveness. JEL Classification: L26, M13, O18, R11